External resistance changes the rotation-extension strategy in accelerated running - Zedler, M.; Pinter, M.; Potthast, W.; Braunstein, B.; Goldmann, J.-P- (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study aimed to investigate the effect of external resistance on running mechanics by comparing unresisted and resisted acceleration tasks. Fourteen elite bobsleigh athletes performed unresisted (bodyweight) and resisted sprints by pushing a loaded sled (85 kg). Ground reaction forces as well as 3D marker trajectories were recorded for five ground contact phases to quantify whole-body posture and rotational and extensional components of forward centre of mass velocity. Resisted acceleration provoked more forward oriented postures (p < .001), and higher extensional velocity components (p < .001) compared to unresisted. Accordingly, the strategy to produce propulsion shifted from rotation to extension in the presence of an external mass. Resisted acceleration exercises are therefore appropriate to stress the extensional component to produce propulsion.